Effectiveness of acyclovir prophylaxis against varicella zoster virus disease after allogeneic hematopoietic cell transplantation: A systematic review and meta‐analysis. Issue 3 (1st March 2019) - Wada‐Shimosato, Yuko; Tanoshima, Reo; Hiratoko, Kanako; Takeuchi, Masanobu; Tsujimoto, Shin‐Ichi; Shiba, Norio; Ito, Shinya; Yamanaka, Takeharu; Ito, Shuichi
Abstract: Background: Varicella zoster virus (VZV) disease is a common complication after hematopoietic cell transplantation (HCT). The mortality rate for disseminated VZV infection is 34%. Acyclovir has been used for the prophylaxis of VZV disease after HCT, but the effectiveness of prophylaxis is controversial. We conducted a meta‐analysis of the incidence of VZV disease within the first 1 year after acyclovir prophylaxis had been discontinued and assessed the risk of VZV disease during acyclovir prophylaxis. Methods: Medline, EMBASE plus EMBASE classics, and the Cochrane Central Register of Controlled Trials were used for a systematic search. The inclusion criteria were both randomized controlled trials and cohort studies that described the effectiveness of acyclovir as prophylaxis against VZV disease after allogeneic HCT. Results: We included seven studies involving a total of 2265 patients. No mortality by VZV was identified. Acyclovir prophylaxis significantly reduced the rate of VZV infection within the first 1 year after discontinuation (risk ratio: 0.38, 95% confidence interval (CI): 0.29‐0.51). The risk of VZV disease during acyclovir prophylaxis was also reduced (risk ratio: 0.17, 95% CI: 0.12‐0.24). Both short–term and long–term prophylaxis reduced the incidence of VZV infection (RR: 0.51, 95% CI: 0.30‐0.86 vs RR: 0.34, 95% CI: 0.22‐0.54). Low–dose acyclovir (<400 mg/d) is sufficient to reduce the risk of VZV disease. Conclusion: This study showed that acyclovir prophylaxis reduced VZV infection after HCT with no fatal cases and acyclovir prophylaxis is beneficial. No significant adverse effects occurred and no delayed VZV disease was identified.